Growth analysis of chub, Leuciscus cephalus (L.), and dace, Leuciscus leuciscus (L.), in the Úpoř stream using growth data of recaptured marked fish - P. Vlach; J. Dušek; M. Švátora; P. Moravec (Czech Journal of Animal Science, 2005)
The length growth of chub and dace was observed. The scale method was used as well as data gained from recaptured individuals which were marked with visible elastomer tags and platinum wire tags with a coloured code placed under the first bony ray of the dorsal fin. The length-weight relationship for chub could be explained by the equation w = 0.00001.l 3.067 (r2 = 0.96). The average condition coefficient reached 1.49. The growth was balanced, gradually slowing down. Von Bertallanffy growth equation had the form Lt = 245.47(1 - e-0.206(t + 0.0333)). The average value of instantaneous monthly growth rate (Gm) ranged between 0.4 and 4.3 (in %). Mean Gm of particular age groups gradually decreased. Gm varied seasonally, annually and in different parts of the stream. The length-weight relationship for dace was w = 0.000009.13.0948 (r2 = 0.97). The mean condition coefficient reached the value of 1.11. The length growth was balanced, gradually decreasing. Von Bertallanffy equation had the form Lt = 216.28(1 - e-0.2536(t + 0.26094)). The instantaneous monthly growth rate ranged between -1.57 and 10.38 (in percentage). This indicator fluctuated according to the age, season and year.